Pengembangan Multimedia Interaktif dengan Model Problem Based-Learning pada Pembelajaran Matematika di Kelas IV Sekolah Dasar - Kinanti, Salsa Phira Putri; Masniladevi, Masniladevi (Universitas Negeri Padang, 2024)
This research is motivated by the limited use of interactive multimedia in mathematics use in elementary schools that use Articulate Storyline 3. The purpose of this research is to produce valid and practical interactive multimedia. This study uses research and development (R&D) methods by using the ADDIE model, this model has five stages, analysis, design, development, implementation, and evaluation. the results of the material, media and language expert validation questionnaire on interactive multimedia with a very valid category score of 91,75%. Based on the teacher and student response questionnaire in the interactive multimedia trial school, it was very practical with a percentage of 95% of teacher responses and 92% of student responses, and the percentage of practicality so that they obtained high value. Thus, it can be concluded that interactive multimedia is valid and practical to use when studying